THE ROLE OF MONETARY POLICY OF THE NATIONAL BANK OF RK IN THE ECONOMIC DEVELOPMENT OF THE STATE - Dzhumabekova, A.T.; Alina, G.B. (Academic Journal of Physical and Chemical Sciences, 2018)
The role of the monetary policy of the National Bank of Kazakhstan in the economic development of the state is increasing, due to the relevance of resource, financial and technological constraints. The study showed a high level of uncertainty over the long-term perspectives. It is extremely important to search for alternatives and to carefully work out various scenarios. Considering the interrelationships of Kazakhstan’s economy to a large extent, involved in world economic relations with the rest of the world, and understanding the impact of monetary policy on macroeconomic indicators, in the authors' opinion, the role of the National Bank of Kazakhstan is increasing. Since the main purpose of monetary policy is to maintain low inflation (at the level of 6-8%). The achievement of these goals will be ens